Evolution: Tracing the origins of centrioles, cilia, and flagella - Carvalho-Santos, Zita (2011)
Centrioles/basal bodies (CBBs) are microtubule-based cylindrical organelles that nucleate the formation of centrosomes, cilia, and flagella. CBBs, cilia, and flagella are ancestral structures; they are present in all major eukaryotic groups. Despite the conservation of their core structure, there is variability in their architecture, function, and biogenesis. Recent genomic and functional studies have provided insight into the evolution of the structure and function of these organelles.